Relations between preschooler social competence and coping tactics during resource‐based conflicts. Issue 4 (12th June 2020) - Nichols, Olivia I.; Vaughn, Brian E.; Coppola, Gabrielle; Shin, Nana; Monteiro, Lígia; Krzysik, Lisa
Abstract: Although peer conflict is a common experience in preschool classrooms, few studies have examined relations between coping with peer conflict and social competence (SC) in preschool samples. In this study, 166 preschoolers (95 male) were observed during dyadic play episodes designed to induce a resource‐based conflict. Coping tactics were coded using Zimmer‐Gembeck and Skinner's framework, and their relations with indicators of SC, assessed using direct observations and sociometric interviews, were tested. On average, dyadic play episodes produced 4.19 conflict events per partner, with children's most common tactics being verbal and/or physical assertions (29% and 17% of all conflict events, respectively). Coping tactics showed moderate correspondence with current taxonomies, and regression analyses with SC demonstrated partial correspondence to studies of older children. Cooperative tactics reflected higher levels of SC, particularly for boys, and failure to cope with the dilemma (i.e., perseveration) reflected lower levels of SC. The use of disengaged tactics was not associated with SC, and only few differences in coping tactic use were associated with the dyad gender composition. Results suggest that coping tactics during resource‐based conflicts among preschoolers are associated with measures of SC and, with slight adjustments, map onto existing frameworks.